Determination of the properties of an experimental glass polyalkenoate cement prepared from niobium silicate powder containing fluoride - Bertolini, Marcio J. [UNESP]; Zaghete, Maria A. [UNESP]; Gimenes, Rossano; Padovani, Gislaine C. [UNESP] (Elsevier B.V., 2008)
Objectives. The purpose of this paper is to modify the conventional calcium fluoro-aluminosilicate glass, which is used in the formation of glass ionomer cements (CIGs) by the niobium addition and to study the properties of GICs obtained.Materials and methods. Sol-gel process was used to prepare the powder at lower temperature than fusion method. Glass-ceramic powder obtained in this way was used to prepare the GICs. The properties such as working and setting times, microhardness and diametral tensile strength were evaluated for the experimental GICs and a commercial luting cement.Results. The ideal powder:liquid (P:L) ratio determined to prepare the experimental GICs was equal to 1:1. The cements prepared using this ratio showed working and setting times similar to the commercial GICs. in mechanical tests it was observed that microhardness and diametral tensile strength of the experimental GICs decreased significantly with the reduction of P:L ratio. on the other hand, the results obtained in microhardness tests indicated that the presence of niobium was a positive factor.Significance. The chemical process allows the development of glass-ceramic powder at 600 degrees C which is the goal of the present paper. It was concluded that GICs containing niobium might be used in dental applications and these results encourage further researches on other compositions. (c) 2007 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: niobium; cement; sol-gel